Behavioural Genetics for Education - Kovas, Yulia; Malykh, Sergey; Gaysina, Darya; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
.
Chapter 1. How Genetics Can Help Education; Yulia Kovas, Tatiana Tikhomirova, Fatos Selita, Maria G. Tosto & Sergey Malykh -- Chapter 2. Gene-Environment Interplay and Individual Differences in Psychological Traits; Philipp Barsky & Darya Gaysina -- Chapter 3. Gene-Environment Correlations in the Context of Parenting and Peer Relationships; Jeffrey Henry, Michael Boivin & Mara Brendgen -- Chapter 4. Behavioural Genetic Studies of Reading and Mathematics Skills; Stephen A. Petrill -- Chapter 5. Studying Rare Genetic Syndromes as a Method of Investigating Aetiology of Normal Variation in Educationally Relevant Traits; Maja Rodic, Darya Gaysina, Sophia Docherty, Sergey Malykh, Kaili Rimfeld, Robert Plomin & Yulia Kovas -- Chapter 6. Self in the Mirror of Behavioural Genetics: Reflections from Twin Studies on Self-Esteem and Self-Concept; Yu L. L. Luo & Huajian Cai -- Chapter 7. The Nature and Nurture of Wellbeing; Claire M. A. Haworth -- Chapter 8. Molecular Genetic Investigations of Personality: From Candidate Genes to Genome-wide Associations; Anastasiya Kazantseva, Sergey Malykh & Elza Khusnutdinova -- Chapter 9. Behavioural Genetic Studies of Child and Adolescent Psychopathology; Elena Gindina & Darya Gaysina -- Chapter 10. Genetic Research on Sleep, Sleep Disturbances and Associated Difficulties; Alice M. Gregory, Michael J. Parsons, Nicola L. Barclay, Philip Gehrman & Rachel E. O$1 (BLeary -- Chapter 11. The Role of Genetic and Environmental Risk Factors in Aetiology of Suicidal Behaviour; Aigul Zainullina, Adelina Valiullina & Elza Khusnutdinova -- Chapter 12. Genetically Informative Investigations of Neurophysiological Traits; Sergey Malykh -- Chapter 13. Conclusion: Behavioural Genomics and Education; Yulia Kovas & Sergey Malykh.s
Keywords: Science; Science; Science, general; Electronic books